2009
DOI: 10.1538/expanim.58.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Air Transportation Cause Physiological and Biochemical Changes Indicative of Stress Leading to Regulation of Chaperone Expression Levels and Corticosterone Concentration

Abstract: Laboratory animals generally experience numerous unfamiliar environmental and psychological influences such as noises, temperatures, handling, shaking, and smells during the process of air transportation. To investigate whether stress induced by air transportation affects stress-related factors in animals, the levels of hormone and chaperone protein were measured in several tissues of F344 rats transported for 13 h and not transported. Herein, we conclude that the levels of corticosterone, HSP70, and GRP78 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…For instance, animal transportation is stressful to rats, and air transportation increases corticosterone (CORT) [35]. Previously, it has been demonstrated that CORT release is positively correlated with sign-tracking behavior in rats and mice [36], [37].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, animal transportation is stressful to rats, and air transportation increases corticosterone (CORT) [35]. Previously, it has been demonstrated that CORT release is positively correlated with sign-tracking behavior in rats and mice [36], [37].…”
Section: Discussionmentioning
confidence: 99%
“…5) In corticosterone-treated animal depression models, increased levels of GRP78 and other endoplasmic reticulum stress-related proteins have been reported in the dentate gyrus and other region. 6,24) These reports suggest that neuronal cell death and endoplasmic reticulum stress may be involved in the pathogenesis of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory animals generally experience numerous unfamiliar environmental and psychological influences such as noises, temperatures, handling, shaking and smells during the process of transportation (Shim et al, 2009). Many studies have found that transport causes significant changes in the parameters used to assess stress and that varying periods of time are required for values to return to baseline levels.…”
Section: Discussionmentioning
confidence: 99%